Lumbar Radiculopathy: a Descriptive Study on Red Flag and Neurologic Symptoms in Dr. Hasan Sadikin General Hospital Bandung - Astrid Feinisa Khairani; Kuheinderan Radha Krishnan; Umar Islami; Siti Aminah Sobana (Global Medical & Health Communication (GMHC), 2020)
Over 80% of the adult population will experience an episode of low back pain (LBP). Low back pain is a pain in the lumbosacral region. When it progresses, which may be identified earlier with signs of a red flag, the manifestation might become radiculopathy. Radiculopathies are nerve root disease which may show signs of neurologic symptoms from the sensory, motoric, or autonomic origin. This study to help identify the clinical characteristics of a red flag in low back pain patients, which became lumbar radiculopathy for prognostic and diagnostic use. It is a descriptive quantitative cross-sectional study of medical records from patients hospitalized with complaints of low back pain with lumbar radiculopathy between January 2013–December 2015 in the Department of Neurology, Dr. Hasan Sadikin General Hospital, Bandung. It identifies a specific red flag and neurogenic symptoms. Patients most affected were housewives (26%), females (60%), and middle-aged adults (31%). The highest recorded symptom being sensory (76%), the highest progression was sensory to motoric (59%), affected by all three neurologic symptoms (39%), and trauma was the highest red flag recorded (48%). Low back pain patients who have signs of red flag show a high tendency to develop radiculopathy, which shows neurologic symptoms. If left untreated earlier, it may become a permanent disability. RADIKULOPATI LUMBAR: STUDI DESKRIPTIF GEJALA KLINIS RED FLAG DAN GEJALA NEUROLOGIS DI RSUP DR. HASAN SADIKIN BANDUNGLebih dari 80% populasi penduduk dewasa akan mengalami episode low back pain (LBP). Low back pain merupakan nyeri pada bagian tulang belakang regio lumbo-sakral. Pada saat rasa sakitnya bertambah berat, gejala berbahaya dapat menjadi awal perkembangan LBP menjadi radikulopati. Radikulopati merupakan penyakit saraf pada daerah radiks neuron berupa gejala sensorik, motorik, dan otonomik. Penelitian ini bertujuan mengidentifikasi karakteristik gejala klinis tanda berbahaya (red flag) pada pasien LBP yang berlanjut menjadi radikulopati lumbar sebagai alat bantu diagnostik dan prognostik. Penelitian ini menggunakan metode penelitian cross-sectional kuantitatif deskriptif dari rekam medis pasien yang dirawat dengan diagnosis LBP dan radikulopati lumbar antara bulan Januari 2013–Desember 2015 di Departemen Ilmu Penyakit Saraf, RSUP Dr. Hasan Sadikin, Bandung. Penelitian ini mengidentifikasi gejala klinis red flag spesifik dan neurologis. Pasien yang terkena terutama ibu rumah tangga (26%), wanita (60%), usia dewasa pertengahan (31%). Gejala yang tercatat paling banyak adalah sensorik (76%), perkembangan progresif sensorik ke motorik (59%), mengalami gangguan ketiganya (39%), dan trauma menjadi penyebab red flag yang paling tinggi (48%). Pasien LBP yang memiliki gejala tanda berbahaya (red flag) memiliki kecenderungan tinggi berkembang menjadi radikulopati yang menunjukkan gejala neurologis. Jika tidak diobati lebih awal, ini dapat mengakibatkan kecacatan permanen.